Pre-qualification of additively manufactured 316L stainless steel using small punch and uniaxial creep testing - Simonovski, I.; Nilsson, K.-F.; Holmström, S.; Kus, M.; García-Junceda, A. (Frontiers in Materials, 2025)
Additive manufacturing represents a cutting-edge technology that offers significant reductions in both manufacturing time and cost. However, any new technology or material must go through a qualification process before it can be used in the nuclear industry. This article reports on a pre-qualification process of 316L stainless steel manufactured using the laser powder bed fusion (LPBF) additive manufacturing process. The study compares LPBF 316L, aged, and non-aged materials from two different manufacturers. A small punch creep test campaign at 650 °C was performed at different loads. These tests are particularly advantageous because they require only a small amount of material, making them ideal when material availability is limited. Additionally, standard uniaxial creep tests were performed at the same temperature for comparative reference. A good correlation for the time to rupture–equivalent stress between the two test types was observed, with the equivalent stress calculated using the Small Punch Test EN 10371:2021 standard. A significant finding is that the small punch creep deflection rate curves for LPBF-manufactured 316L exhibit multiple minima, unlike the single minimum observed in forged 316L. This is believed to result from micro-cracking and has important implications for determining the equivalent stress creep properties, which are based on the single minimum value in the EN 10371:2021 standard. The multiple minima finding suggests that the approach used to determine equivalent stress and strain rate in small punch creep tests in the EN 10371:2021 standard must be re-evaluated to accommodate this complexity.